As formas institucionais da violência: controle, vigilância, cerceamentos e repressão política no estado de São Paulo de 1954 a 1960 - Feltrim, Luciana da Conceição (2012)
The aim of this study is to analyze the performance of Department Political and Social Order of São. Paulo (DOPS/SP) between 1954 and1961 through the analysis of the reports prepared bay of the officers of the DOPS, existing in the Public Archives of the São Paulo State; in training manuals for police, and in the newspaper. Such reports, in the mentioned period be important not only for the information they contain about the logic of such surveillance and repression, as the power to compose and tool files or even initiate police investigations against those accused of subversion. The research has as central debates about the legal framework that allows criminalization of union protests and the curtailment of civil society in the period 1950 to 1960. We show how the repressive system was manifested in the State of São Paulo, from surveillance and repression carried out by police in all municipalities based on an integrated basis with the DOPS. The analytical procedure that was endorsed through of immanent analysis, to be respected completeness of the information which is not assigned a priori meanings, which allows the elucidation of at least some of the links constituting the social dynamics in their concreteness. It is evident so what were the guidelines that the police received, as they did, what were the reasons of the surveillance, who they were watching, the ideology that they expressed, not taken as individuals, but while the government apparatus, in the intrinsic and complex inside logical which sets the state in Brazil